HOXA10 promote pancreatic cancer progression via directly activating canonical NF-κB signaling pathway. (12th May 2022) - Li, Jiao; Chang, Jing; Wang, Jinghan; Xu, Dapeng; Yang, Minwei; Jiang, Yongsheng; Zhang, Junfeng; Jiang, Xiaohua; Sun, Yongwei
Abstract: Background: Although transcription factor homeobox A10 (HOXA10) plays an important role in regulating the development of the pancreas, a pathway of HOXA10 participates in pancreatic ductal adenocarcinoma (PDAC) progression has not been revealed. Methods: Immunohistochemistry assays were applied to demonstrate the relationship between HOXA10 expression and PDAC progression. Functional assays were used to illustrate the oncogenic role of HOXA10 in PDAC progression. Regulatory mechanisms of HOXA10 induced IKKβ gene transcription and the nuclear transcription factor kappa B (NF-κB) signal pathways activation were also investigated in PDAC cells. Results: In the current study, we show that HOXA10 expression increased in PDAC with higher tumor stage and poor patient survival in public RNA-seq data suggesting HOXA10 is associated with PDAC progression. HOXA10 promotes PDAC cell proliferation, anchorage colony formation, and xenograft growth by activating canonical NF-κB signaling both in vitro and in vivo . Mechanically, HOXA10 up-regulates IKKβ gene transcription directly and subsequently sustain the activation of NF-κB independent of tumor necrosis factor-alpha in PDAC cells. Conclusion: Collectively, up-regulation of HOXA10 gene expression promote cell growth and tumor progression through directly activating canonical NF-κB signaling in PDAC. Abstract : Our study provides evidence supporting HOXA10 up-regulation in human PDAC might plays an important role in the acquisition of a poor prognosis phenotype. This suggested that in PDAC, HOXA10 functions as an oncoprotein and may be utilized as a novel potential prognosis biomarker. Furthermore, the functional and mechanistic studies indicated that HOXA10 exert its function in controlling PDAC by activating the NF-κB signaling pathway. Therefore, understanding the biological function and molecular mechanisms of HOXA10 in tumor progression may provide a new insight that HOXA10 may serve as a potential therapeutic target for PDAC. Graphical Abstract: